2021
DOI: 10.6017/ital.v40i2.12629
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the Use of Academic Library Resources

Abstract: The COVID-19 pandemic has greatly impacted higher education, including academic libraries. This paper compares the use of library resources (including interlibrary loan, website and discovery tool pageviews, database use, patron interactions, etc.) at three university libraries before and after the pandemic. The latter part of the 2019 and 2020 spring semesters are the time frames of focus, although two control time frames from earlier in those semesters are used to determine how the semesters differed when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 5 publications
2
30
3
Order By: Relevance
“…In addition, the use of the LibGuides Database A to Z list, increased in use in 2020/21 compared to the two previous years. This finding is in contrast to the previous study indicating that both NEIU and Valparaiso reported a decrease in views (Connell et al, 2021). COVID-19 also influenced users' interactions with librarians.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, the use of the LibGuides Database A to Z list, increased in use in 2020/21 compared to the two previous years. This finding is in contrast to the previous study indicating that both NEIU and Valparaiso reported a decrease in views (Connell et al, 2021). COVID-19 also influenced users' interactions with librarians.…”
Section: Discussioncontrasting
confidence: 99%
“…However, some institutions would Impact of COVID-19 on academic library not have been filling during some periods of the pandemic. LSU noted a 35% increase in requesting articles from other libraries while Valparaiso observed a 14% decrease (Connell et al, 2021). It is possible that student use of the service decreased while faculty remained largely unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Academic libraries provide key services in supporting teaching, learning and research within and outside the aegis of the academic institution. Connell, Wallis, and Comeaux (2021) argue that historically libraries have proved their capacity to comprehend and apprehend the need for preparedness in the event of an outbreak of disasters. However, the outbreak of the COVID-19 pandemic caught many institutions unaware and without a clue as to how they should respond.…”
Section: Problem Statementmentioning
confidence: 99%
“…Several studies have investigated students' use of library resources during the COVID-19 pandemic (Shi et al. , 2021; Connell et al. , 2021; De Groote and Scoulas, 2021; Dadhe and Balkundi, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Connell et al. (2021) also attempted to provide insight into students' library use during the COVID-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%